An Inquiry into the North-South Management Gap in China - Yong Soo Keong; Partha Sen; Cao Jing (Center for Economic Studies and ifo Institute (CESifo), 2024)
We identify a puzzling management practice gap in China. In the South, a one standard deviation increase in firms' management competency is associated with a 7.5 percent improvement in sales productivity and a 29.2 increase in profitability. But such associations are muted for firms located in the North. The southern firms outperformed the northern firms by 8.1 percent in management practices and in all aspects of administration. We conjecture this is partially related to the convenience of accessing a larger export market in the South. The gap persists even after controlling for known sources of heterogeneity such as firm characteristics and resources. After decomposition, a difference of 6.6 percent in management quality remains unexplained. Remarkably, Northern firms' management is correlated with mitigating environmental externalities but not for Southern firms. Our study contributes to the understanding of management that is potentially due to regional differences in social norms and institutional factors.
Keywords: D22; M10; M20; Q40; Q50; 330; management practices; productivity; export